Modeling the Cost and Outcomes of Pharmacist-Prescribed Emergency Contraception - Marciante, Kristin D. (© American Journal of Public Health 2001, 2001)
Objectives. This study investigated the effect on the risk and cost of unintended pregnancies of emergency contraceptive pills obtained directly from a pharmacist. Methods. We used a decision model to compare outcomes for private and public payers following unprotected intercourse from. Results. Obtaining emergency contraceptive pills from a pharmacy, compared with obtaining them from a physician or clinic, resulted in a $158 (95% confidence interval (CI) = $76, $269) reduction in costs for private payers and a $48 (95% CI = $16, $93) reduction for public payers. Conclusions. Our findings suggest that under varied assumptions, obtaining emergency contraceptive pills directly from a pharmacist reduces the number of unintended pregnancies and is cost saving.